Diagnosis and Prognostic Analysis of Mycoplasma pneumoniae Pneumonia in Children Based on High-Resolution Computed Tomography. (22nd April 2022) - Leng, Jiangang; Yang, Zemin; Wang, Wenhui
Abstract : Mycoplasma pneumoniae (MP) is defined as a common cause of pulmonary infections and accounts for up to four over ten of pneumonia in children over age 5. This study was aimed to explore the diagnosis and prognosis of mycoplasma pneumoniae pneumonia (MPP) in children using high-resolution computed tomography (CT) (HRCT). 71 children hospitalized with MPP were undertaken as the research objects to observe the incidence rate, occurrence time, and duration of the clinical symptoms and pathological signs. The chest HRCT and pulmonary ventilation function (PVF) were examined in the acute phase, the second phase re-examination period, and the third phase re-examination period. Relevant indicators were statistically analyzed to determine the change rules of chest HRCT and PVF and correlation between the two. Clinically, the children with MPP suffered from fever, cough, and sore throat. In addition to the above symptoms, children with MPP had different degrees of PVF impairment. Compared with the group with normal HRCT results, the forced vital capacity (FVC), forced expiratory volume in 1 second (FEV1), peak expiratory flow (PEF), forced expiratory flow at 25% forced expiratory volume (FEF25), forced expiratory flow at 50% forced expiratory volume (FEF50), forced expiratory flow at 75% forced expiratory volume (FEF75), and maximum mid-expiratory flow (MMEF75/25) of children in bronchopneumonia group, segmental pneumonia group, and lobar pneumonia group were obviously reduced, showing statistically great differences ( P  < 0.05). Compared with the case in acute phase, the PVF indicators of children in the re-examination phases were much higher, with greatly statistical differences ( P  < 0.05). In children with MPP, both the large and small airways were affected, but the recovery of the small airways was slow. Pulmonary HRCT and PVF can be undertaken as important indicators to judge the severity and prognosis of MPP in school-age children.